2022
DOI: 10.1039/d2dt00054g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic amination of lactic acid using Ru–zeolites

Abstract: Ru supported on zeolite catalysts: a case study for the direct amination of biobased alpha-hydroxy acids into alpha-amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Afterwards, extensive research efforts were devoted to develop highly efficient thermocatalytic systems for amino acid synthesis from α-hydroxyl acids. [49][50][51][52] For example, Xie et al reported that N-doped carbon nanotube-supported Ru nanoparticles (Ru/N-CNTs) exhibited a remarkable performance in the amination of lactic acid, in which the maximum alanine yield of 70% was obtained at 180 °C and 10 bar H 2 for 2 h. 52 The outstanding activity of the Ru/N-CNT catalyst was mainly attributed to the highly dispersed Ru nanoparticles, the strong electronic interaction between Ru nanoparticles and N-CNTs, and the enhanced adsorption of lactic acid through basic sites. Xin et al prepared a magnetic catalyst Ru/Ni@C by ethylene glycol reduction of metal Ru supported on encapsulated Ni@C. 51 The best catalytic performance was obtained with a lactic acid conversion of 70% and an alanine yield of 64% at 200 °C and 15 bar H 2 for 2 h. The formed RuO 2 species, acting as Lewis acid sites, could improve the activation of the hydroxyl group of lactic acid as well as the adsorption ability of NH 3 , accordingly facilitating the amination of lactic acid to alanine.…”
Section: Biological Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Afterwards, extensive research efforts were devoted to develop highly efficient thermocatalytic systems for amino acid synthesis from α-hydroxyl acids. [49][50][51][52] For example, Xie et al reported that N-doped carbon nanotube-supported Ru nanoparticles (Ru/N-CNTs) exhibited a remarkable performance in the amination of lactic acid, in which the maximum alanine yield of 70% was obtained at 180 °C and 10 bar H 2 for 2 h. 52 The outstanding activity of the Ru/N-CNT catalyst was mainly attributed to the highly dispersed Ru nanoparticles, the strong electronic interaction between Ru nanoparticles and N-CNTs, and the enhanced adsorption of lactic acid through basic sites. Xin et al prepared a magnetic catalyst Ru/Ni@C by ethylene glycol reduction of metal Ru supported on encapsulated Ni@C. 51 The best catalytic performance was obtained with a lactic acid conversion of 70% and an alanine yield of 64% at 200 °C and 15 bar H 2 for 2 h. The formed RuO 2 species, acting as Lewis acid sites, could improve the activation of the hydroxyl group of lactic acid as well as the adsorption ability of NH 3 , accordingly facilitating the amination of lactic acid to alanine.…”
Section: Biological Synthesismentioning
confidence: 99%
“…However, high reaction temperature (>180 °C) is necessary to overcome the energy barrier for the dehydrogenation of hydroxyl groups of α-hydroxyl acids, which will in turn induce the formation of side products, such as ethanol, propionic acid, and propenamide. 11,49 Therefore, developing high-efficient and selective catalysts for amino acid synthesis at low temperatures is highly desirable for future research.…”
Section: Biological Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14] It is worth noting that lactic acid can be converted to alanine in ammonia solution when H 2 is involved, and the commonly used catalyst for the hydrogenation of lactic acid to alanine was Ru species supported on carbon nanotubes, MgO, and zeolites. [15][16][17][18][19][20] Alanine is an important amino acid, which is widely used in food, biology, medicine and other fields. Inspired by this, by using 2 wt% Ru/TiO 2 as the catalyst, researchers realized the direct conversion of PLA to alanine in ammonia solution using a one-pot method, and the reaction did not require H 2 participation.…”
Section: Introductionmentioning
confidence: 99%
“…The migration from a petroleum-based chemical industry can be assisted by the development of processes that produce and convert platform molecules derived from renewable carbon sources. [1][2][3][4][5] Biomass serves as one of the most promising renewable sources for high-value chemicals. [6][7][8][9][10] An example of such a high-value chemical is 2,4-hexenedioic acid, known as muconic acid (MA).…”
Section: Introductionmentioning
confidence: 99%